The influence of social media in the digitalization era on the motivation and interest of UMKM actors in developing businesses in Kabanjahe - Elsera, Hilda; Hartati, Sri (Institute of Computer Science (IOCS), 2024)
This study aims to determine the effect of implementation of social media on the development of Micro small and medium enterprises (MSMEs), the influence of social media to increase MSME marketing, and social media influence on productivity improvement of MSMEs. This study using structured interviews, in-depth interviews and observations of MSMEs and social media are used. Subjects in this study were owners, managers and employees of MSMEs were selected by purposive sampling. The study concludes that MSMEs are observed have been using social media in the company. Social media is the most widely used Instagram, TikTok, Facebook, and Twitter.